A Plausible Role for Collectins in Skin Immune Homeostasis - Wang, Tian; Li, Ke; Xiao, Shengxiang; Xia, Yumin (Frontiers in Immunology, 2021)
The skin is a complex organ that faces the external environment and participates in the innate immune system. Skin immune homeostasis is necessary to defend against external microorganisms and to recover from stress to the skin. This homeostasis depends on interactions among a variety of cells, cytokines, and the complement system. Collectins belong to the lectin pathway of the complement system, and have various roles in innate immune responses. Mannose-binding lectin (MBL), collectin kidney 1, and liver (CL-K1, CL-L1) activate the lectin pathway, while all have multiple functions, including recognition of pathogens, opsonization of phagocytosis, and modulation of cytokine-mediated inflammatory responses. Certain collectins are localized in the skin, and their expressions change during skin diseases. In this review, we summarize important advances in our understanding of how MBL, surfactant proteins A and D, CL-L1, and CL-K1 function in skin immune homeostasis. Based on the potential roles of collectins in skin diseases, we suggest therapeutic strategies for skin diseases through the targeting of collectins and relevant regulators.